Evaluation of microbial resistance of enterobacteria isolated from beach water in São José de Ribamar - MA (Research, Society and Development, 2022)
This study aimed to evaluate the bacteriological quality of the water of the beach of São José de Ribamar / MA in the dry and rainy periods, the species of the family Enterobacteriaceae in the water were also identified, verifying their resistance against commercial antibiotics. The water samples were collected at three points on the beach and sent to be analyzed at the Laboratory of Food and Water Microbiology at the Federal University of Maranhão. Identification of Enterobacteriaceae was performed, according to the methodology described in APHA - Standard Methods for the examination of Water and Wastewater. Ph and salinity measurements being submitted to conventional antibiotics ampicillin (AMP, 10 μg), gentamicin (GEN, 10 μg), chloramphenicol (CLO, 30 μg) and pipemidic acid (PIP, 30 μg)), where the method of disk diffusion. PH and salinity measurements were also carried out. Through biochemical identification, 11 species were presented and Escherichia coli was observed in a higher percentage in both periods. In addition, through MDD, the species Citrobacter koseri was the only one that showed sensitivity to all antibiotics and all bacteria showed an antimicrobial profile sensitive to chloramphenicol. According to the species found, significant contamination can be observed on the beach of São José de Ribamar.